Comparison of Mechanical and Thermal Properties of Polyamide-66/Rubber/Fiber Alloy Composites - Lee, Ji-Eun; Han, Dong-Hun; Kim, Young-Min; Choi, Kyung-Man (Asian Journal of Chemistry, 2013)
This study compared and evaluated the mechanical and thermal properties of three-phase blends of polyamide-66. A series of polyamide-66/polymer blends were prepared using an extrusion and injection process and the blending polymers were rubber, TPU, polyester block polyamide and ionomer. The polymer contents was 10-30 %. The blending polymers were used to improve the moisture absorbance and elastic recovery of polyamide-66. The coupling agent impregnated in the glass fiber was melt blended to increase the miscibility of each composition.